Two Neural Measures Differ between Urban and Rural Song Sparrows after Conspecific Song Playback - Sewall, Kendra B.; Davies, Scott (Frontiers in Ecology and Evolution, 2017)
Urbanization is a critical form of environmental change that can affect the physiology and behavior of wild animals and, notably, birds. One behavioral difference between birds living in urban and rural habitats is that urban males show elevated boldness or territorial aggression in response to simulated social challenge. This pattern has been described in several populations of song sparrow, Melospiza melodia. Such behavioral differences must be underpinned by differences in the brain, yet little work has explored how urbanization and neural function may be interrelated. We explored the relationship between urbanization and neural activation within a network of brain regions, collectively called the social behavior network, which contributes to the regulation of territorial aggression. Specifically, we captured free-living, territorial male song sparrows by playing them conspecific songs for 6-11 minutes, and then collected their brains. We estimated recent neural activation, as indicated by the immediate early gene FOS, and measured levels of a neuropeptide, arginine vasotocin (AVT), which is involved in the regulation of social behavior. Based on previous studies we expected urban males, which are generally more territorially aggressive, to have lower FOS expression in a node of the social behavior network implicated in regulating territoriality, the lateral septum (LS). Additionally, we expected urban males to have lower AVT expression in a brain region involved in the regulation of sociality, the medial bed nucleus of the stria terminalis (BSTm). We found that, compared to rural males, urban male song sparrows did have lower FOS expression in the LS. This pattern suggests that lower neural activation in the LS could contribute to behavioral adjustments to urbanization in male song sparrows. Additionally, counter to our predictions, urban male song sparrows had higher AVT-like immunoreactivity in the BSTm. Future work building upon these findings is needed to determine the causal role of such neural differences across rural and urban habitats. Understanding the mechanisms impacted by urbanization will inform our understanding of the reversibility and consequences of this form of habitat change.